Orbital Rotation of Trapped Particle in a Transversely Misaligned Dual-Fiber Optical Trap - Guangzong Xiao; Kaiyong Yang; Hui Luo; Xinlin Chen; Wei Xiong (IEEE Photonics Journal)
We propose and demonstrate a novel optical orbital rotation technique for trapped particle in a transversely misaligned dual-fiber optical trap. The orbital rotation frequency can be controlled by varying the power of two counterpropagating beams. We theoretically analyze an optical force field exerted on a trapped 10- $μm$ -diameter polystyrene particle and simulate its dynamic trajectory within a geometric optics regime framework. Results show that orbital rotation is realized by an optical force field with a vortex distribution that inherently stems from a transversely misaligned dual-fiber optical trap. The orbital rotation trajectory of the particle depends on the configuration of the transversely misaligned dual-beam optical trap rather than its initial position.